Brand Love – Moving Beyond Loyalty An Empirical Investigation of Perceived Brand Love of Indian Consumer - Amanpreet Kang (Arab Economic and Business Journal, 2015)
Each passing day brings new brands to India each vying for a share of wallet in the prospering market. By 2020, the median age of Indian population will be 29 years and owing to the absolute population of India, the presence in Indian market will be rewarding for the multinationals. But the twenty-something targets, because of their "variety seeking"disposition, are a challenge, even for the most experienced marketers. The marketers create brands with a vision to create sustained loyalty, which however gets diluted by consumers coveting for "something new"and "something different". As a defensive, the marketers are now attempting to create an emotional bond with the customers. This phenomenon is termed as brand love and it is likely to influence desirable marketing outcomes such as commitment, positive word of mouth by customers, etc. This research attempts to explore the perceived "brand love" of young Indians. A structured, non-disguised questionnaire was used, data was collected through personal interviews and a total of 160 complete questionnaires were obtained. The findings describe the comparative status of brands loved by the Indian consumers and will help marketers to understand their perceived brand image, customer engagement and attitude of customers towards their brands.
Keywords: 650; Brand Love; Customer Satisfaction; Customer Loyalty; Brand Image; India; Smartphones